RETRACTED ARTICLE: On-Farm study on wastewater reuse in vegetable cultivation - Karnchanawong S. (2017)
The objective of this study was to investigate harvesting rates of vegetables irrigated with domestic wastewater (RW) and primary treatment effluent (PE). The groundwater (GW) was also concurrently used as control. Four popular vegetables had been cultivated on-farm during June 2004 - November 2005. It was found that the amounts of irrigated water varied according to seasons, with ratios of irrigated water: total water inputs ranging from 0.03 to 1.00. The harvesting rates of Chinese kale in RW- and PE- plots were statistically different (P < 0.05) and higher than GW-plot in the 2 nd - 4 th cultivation. For cauliflower, there was no statistically different in harvesting rates among plots irrigated with RW, PE and GW in 4 cultivation. The harvesting rates of Petsai Chinese cabbage in 2 crops were higher in RW- and PE-plots. They were statistically different (P < 0.05) from those irrigated with GW. For Chinese radish, harvesting rate of PE-plot was statistically different (P < 0.05) in the 1 st cultivation. In the 2 nd cultivation, harvesting rate of RW- plot was statistically different (P < 0.05) while the 3 rd and 4 th cultivation had no statistically different in all plots. The toxicity on vegetable growth due to RW and PE was not observed throughout the study. In terms of plant's growth, RW and PE are suitable for vegetable cultivation while harvesting rates can be expected to be similar to or higher than those irrigated with groundwater. © 2011 IEEE.